Across this land : a regional geography of the United States and Canada - Hudson, John C. (Baltimore Johns Hopkins University Press, 2020)
"Geographer John C. Hudson provides a comprehensive regional geography of North America (US and Canada) in the second edition of Across This Land. The new edition incorporates the latest data available and updated place names, along with general revisions throughout. He divides the continent into ten regions: Atlantic Canada and Quebec, the Northeast, the Upland South, the Lowland South, the Middle West, the Central Plains, the Western Plains and Rocky Mountains, the Intermountain West, the North, and the Pacific Realm. These regions are then subdivided into twenty-seven smaller areas. Hudson considers the physical, political, human, and historical geography of each"--
Includes bibliographical references and index.
Keywords: Regionalism -- North America; Regionalism -- United States; Regionalism -- Canada; North America -- Geography; United States geography; Canada -- Geography